Analysis of Determinant Factors Affecting Patient Satisfaction Levels at Lingsar Community Health Center (PT. LARPA JAYA PUBLISHER, 2024)
Patient satisfaction in the health service industry is an important factor for developing a service provider system that can offer fast response to patient needs, minimize budget and time, and maximize the impact of service on all targets. Factors that can influence patient satisfaction are product quality, service quality, emotionality, price and cost. The aim of this research was to analyse the determinant factors that influence the level of patient satisfaction at Lingsar Community Health Center. The sampling technique used was simple random sampling with a total of 94 respondents. The method employed in this research was quantitative method. The result of the research showed that the P value was <0.005 which indicated that there was a significant influence between the determinant factors and patient satisfaction. The result of the coefficient determination test (R2) showed that the product quality had the greatest influence on patient satisfaction at 2.93 followed by price at 2.92. On the third place was service quality at 2.74 followed by emotion and cost at 2.19 and 2.09 respectively. These findings show that good satisfaction factors can provide a good level of patient satisfaction. Thus, patients who came for treatment to Lingsar Community Health Center would feel comfortable. To conclude, good product quality from Health Center plays an important role to maintain patient satisfaction.